2016
DOI: 10.3390/molecules21060742
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of C2-Symmetric Benzimidazolium Salts and Their Application in Palladium-Catalyzed Enantioselective Intramolecular α-Arylation of Amides

Abstract: A series of C 2 -symmetric chiral benzimidazolium salts, the precursor of N-heterocyclic carbene ligands, were designed and synthesized from 1,2-dibromobenzene. In situ prepared corresponding carbenes were tested in the asymmetric palladium-catalyzed intramolecular α-arylation of amides, affording chiral diarylmethanols with high yields and moderate enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…73 One year later, Shi and Li found that their synthesized C2-symmetric chiral benzimidazolium salts L26-L29, in conjunction with [Pd(allyl)Cl] 2 , efficiently catalyzed the synthesis of chiral diarylmethanol derivatives with high yields and moderate enantioselectivities (Scheme 45). 74 In 2018, Gandhi and coworkers presented the synthesis of fluorene-based mono-and bimetallic Pd-PEPPSI complexes (56)(57)(58)(59)(60)(61) which were demonstrated to be effective for the one-pot sequential a-arylation/alkylation of oxindoles (Fig. 10).…”
Section: Metal-nhc Catalyzed A-arylation Of Amidesmentioning
confidence: 99%
See 1 more Smart Citation
“…73 One year later, Shi and Li found that their synthesized C2-symmetric chiral benzimidazolium salts L26-L29, in conjunction with [Pd(allyl)Cl] 2 , efficiently catalyzed the synthesis of chiral diarylmethanol derivatives with high yields and moderate enantioselectivities (Scheme 45). 74 In 2018, Gandhi and coworkers presented the synthesis of fluorene-based mono-and bimetallic Pd-PEPPSI complexes (56)(57)(58)(59)(60)(61) which were demonstrated to be effective for the one-pot sequential a-arylation/alkylation of oxindoles (Fig. 10).…”
Section: Metal-nhc Catalyzed A-arylation Of Amidesmentioning
confidence: 99%
“…79 Known catalytic C-S bond-cleavage reactions required large amounts of catalysts (over 2 mol%, but generally 5-20 mol%) 80 Scheme 45 Chiral NHC precursors in the palladium catalyzed intramolecular cyclization of amides into oxindoles, as described by Shi and Li. 74 Fig. 10 Mono-and bis(palladium)-PEPPSI complexes described by Gandhi et al 75 Scheme 46 Coupling between aryl halides and N-substituted oxindoles.…”
Section: A-arylation Of Carbonyl Compounds With Pseudo-halide Substratesmentioning
confidence: 99%
“…The NHC complexes were synthesized from enantiomerically-pure benzimidazolium salts (1a-g), which in turn can be prepared by following our previous articles [36,37]. Among the NHC precursors prepared, compounds 1c and 1d were new and are reported for the first time in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…The NHC precursors 1a-g were synthesized following our previous paper [36], and the 1 H NMR spectra of 1a-b and 1e-f were identical to those reported in the literature [36,37] …”
Section: Preparation Of Benzimidazolium Salt 1a-gmentioning
confidence: 99%
“…15 Since Berners-Price reported the anticancer properties of Au(I)-NHC complexes in 2004, 16 considerable efforts have been dedicated to the investigation of metal NHC complexes, such as Au, Ag, Pd, Pt, Cu, Ru, and Ir, as antineoplastic agents. [17][18][19][20][21][22] In combination of our interest in the development of novel NHCs ligands [23][24][25][26][27][28] and our experience with benzimidazole carbenes, [29][30][31] we herein report a new route for the synthesis NHC-Rh complexes with benzimidazole backbone using simple 1,2-dibromobenzene as starting material. Considering the promising potential of rhodium complexes as therapeutic molecules, [32][33][34][35][36][37][38][39] these new complexes were evaluated for cytotoxicity against MCF-7 human breast cancer cells and most of the synthesized complexes showed excellent activities.…”
Section: Introductionmentioning
confidence: 99%